Deep Sequencing Revealed a CpG Methylation Pattern Associated With ALDH1L1 Suppression in Breast Cancer - Beniaminov, Artemy D.; Puzanov, Grigory A.; Krasnov, George S.; Kaluzhny, Dmitry N.; Kazubskaya, Tatiana P.; Braga, Eleonora A.; Kudryavtseva, Anna V.; Melnikova, Nataliya V.; Dmitriev, Alexey A. (Frontiers in Genetics, 2018)
Hypermethylation of promoter CpG islands is generally recognized epigenetic mechanism responsible for gene silencing in cancer. However, molecular details on how this epigenetic mark triggers the process of gene downregulation are still elusive. Here, we used deep bisulfite sequencing and qPCR analysis to investigate the pattern of CpG methylation of ALDH1L1 promoter region and its association with the gene expression level in 16 paired breast cancer samples of different clinical stages. Expression of ALDH1L1 gene was suppressed in all examined breast cancer samples up to 200-fold, and average hypermethylation level of the promoter region correlated positively with ALDH1L1 downregulation (Spearman’s correlation coefficient, rs = 0.38). We determined the role of every individual CpG site within the ALDH1L1 promoter, including upstream untranscribed region, first untranslated exon, and the start of the first intron, in aberrant gene expression by correlation analysis. The search revealed CpG sites which methylation has the highest impact on intensity of gene transcription. The majority of such CpG sites are located in a compact region in the first intron of the ALDH1L1 gene. These results assist in unraveling of dynamic nature of CpG promoter hypermethylation as well as demonstrate the efficiency of deep bisulfite sequencing in search for novel epigenetic markers in cancer.